2010
DOI: 10.1242/dev.053421
|View full text |Cite
|
Sign up to set email alerts
|

Pitx2 defines alternate pathways acting through MyoD during limb and somitic myogenesis

Abstract: SUMMARYThe MyoD gene is part of the core regulatory network that governs skeletal myogenesis and acts as an essential determinant of the myogenic cell fate. Although generic regulatory networks converging on this gene have been described, the specific mechanisms leading to MyoD expression in muscles of different ontology remain misunderstood. We now show that the homeobox gene Pitx2 is required for initial activation of the MyoD gene in limb muscle precursors through direct binding of Pitx2 to the MyoD core en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 72 publications
4
59
0
Order By: Relevance
“…5C-E). When we examined the localization of the homeobox transcription factors Pitx2, a marker of muscle progenitors required for activation of MyoD (Shih et al, 2007;L'Honore et al, 2010), and Hoxa7, a gene involved in patterning of the upper thoracic region (Chen et al, 1998), we found these to be expressed in the muscle cells surrounding the elbow as well as in the cartilage of the elbow joint itself (Fig. 5F,G).…”
Section: Resultsmentioning
confidence: 99%
“…5C-E). When we examined the localization of the homeobox transcription factors Pitx2, a marker of muscle progenitors required for activation of MyoD (Shih et al, 2007;L'Honore et al, 2010), and Hoxa7, a gene involved in patterning of the upper thoracic region (Chen et al, 1998), we found these to be expressed in the muscle cells surrounding the elbow as well as in the cartilage of the elbow joint itself (Fig. 5F,G).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, numerous cis-regulatory regions of animal genes have been shown to contain multiple enhancers with overlapping or very similar expression patterns (Jeong et al, 2006;Werner et al, 2007;Hong et al, 2008;McGaughey et al, 2008;Corbo et al, 2010;Frankel et al, 2010;Kalay and Wittkopp, 2010;L'Honore et al, 2010;Naranjo et al, 2010;Perry et al, 2010Perry et al, , 2011Franchini et al, 2011;Galindo et al, 2011;Ghiasvand et al, 2011;Lee et al, 2011;McBride et al, 2011;Watts et al, 2011;Pauls et al, 2012). Yet, the first observations of overlapping expression from different enhancers date back from the 1990s (Hoch et al, 1990;Kassis, 1990;Tolias and Kafatos, 1990).…”
Section: Genes Have Multiple Enhancers With Overlapping or Very Similmentioning
confidence: 99%
“…Delamination of PAX3-positive myoblasts from the ventrolateral dermomyotome is induced by hepatocyte growth factor (HGF)/Scatter factor, which causes cells to migrate into the developing limb buds as shown by the overexpression of HGF in chicken embryos and loss of function of MET (c-met), the HGF receptor, in mice (Bladt et al 1995, Brand-Saberi et al 1996, Scaal et al 1999. The migrating muscle cells form two blocks of tissue, the dorsal and ventral muscle masses, and only then do they begin to differentiate and express musclespecific genes, a process requiring the transcription factors MEOX2 and PITX2 (Mankoo et al 1999, L'Honoré et al 2010. This process is shown schematically in Fig.…”
Section: Development Of Limb Musclesmentioning
confidence: 99%